(untitled) (The Journal of Psychology and Sociology, 2016)
The article discusses the concept of sustainable development in economic, social and environmental aspects. Network society with global capitalism does not correspond to the principles of sustainable development. In the «electronic-controlled global casino» the market logic does not work for financial flow. As an alternative model of global capitalism are analyzed the A. Ryh’s theoretical model of economic ethics and practice of Islamic economics as an example of Islamic finance and Islamic banking. According to Rih, the fundamental purpose of economy (econ-omy system) is to serve the life, being as a survival tool for human. The humane aim of the Economy is to create conditions for a decent human existence- status of the person involved in overall work process, defining this process and supporting public share responsibility for it. The public aim of the economy is that economics benefits are distributed fairly as possible, as the use of the social product was available as the maximum allowable for the most disadvantaged and highest level of education opportunities according to the abilities. Man as a part of the created world, but not a “crown” of the creation, is in-cluded in the interconnected and interdependent nature of the environmental body. In Islamic world man acts only as the manager of all resources owned by Allah. Man strives for success through the observance of religious laws, but economic activity – is only a part of his religious duties. Actively participating in economic activities, a Muslim brings great benefit to Islam and society. Financial and economic activities in Islam are always connected with soci-ety, with common good and individual benefit. Islamic economic system acts on the principle: production – according to possibilities, consumption – for piety. The Islamic financial system is based on the following principle: capital gains; invest-ments- in the real economy sector (production and trade), deals with real assets; partnership with spread risks and profits; money – is a measure of a cost. The advantages of Islamic banking are in the fair spreading risks between inves-tors and borrowers, in stable financial institutes, the absence of integrated market of liabilities and sustainability. Threats of the Islamic banks are that there is no experience in implementation on the post-Soviet space, a lack of qualified experts in the field of Is-lamic banking, in the lack of interest of businessmen in joining into their business share capital, the lack of quality investment projects and companies, in a wrong attitude to Islamic products, in the low literacy level in the field of Islamic finance. The most com-mon myths are about charity, free of charge of Islamic banking, new way of the Islam-ization, financing the terrorism and specific Muslims’ banks. Steady, stable, transparent Islamic financial system and the economy can become an actual model of development and advanced experience for sustainable development in many countries of the world.